Effect of substrate bias voltage parameters on surface properties of ta-C coatings - Safonov, V.; Miroshnichenko, K.; Zykova, A.; Zavaleyev, V.; Walkowicz, J.; Rogowska, R. (Вопросы атомной науки и техники, 2017)
The study presents the technology of the formation of amorphous ta-C films, deposited by pulsed vacuum-arc method with the use of a water-cooled electromagnetic Venetian blind plasma filter. The effect of the substrate bias voltage, in the range of -25 to -200 V, on the structural and surface properties of ta-C coatings was analyzed. The strong correlation between surface properties of amorphous ta-C films depending on substrate bias voltage variations and characteristic changes in the content of the diamond-like sp³ fraction was observed. Представлена технология формирования аморфных покрытий ta-C, нанесенных импульсным вакуумно-дуговым методом с использованием охлаждаемого электромагнитного фильтра плазмы. Проанализирован эффект изменения смещения потенциала подложки в диапазоне значений от -25 до -200 В и его влияние на структурные и поверхностные свойства покрытий ta-C. Обнаружена корреляция между поверхностными свойствами аморфных покрытий ta-C и изменениями в содержании sp³-фазы в зависимости от изменения потенциала подложки. Наведена технологія формування аморфних покриттів ta-C, нанесених імпульсним вакуум-дуговим методом з використанням охлаждаемого електромагнітного фільтра плазми. В роботі був проаналізований ефект зміни зміщення потенціалу підкладки в діапазоні значень від -25 до -200 В і його вплив на структурні і поверхневі властивості покриттів of ta-C. Була виявлена кореляція між поверхневими властивостями аморфних покриттів ta-C і змінами в змісті sp³ фази в залежності від зміни потенціалу підкладки.